A synthetic enzyme built from DNA flips 107 lipids per second in biological membranes - Alexander Ohmann (Nature Portfolio, 2018)
Mimicking enzyme function and improving upon it is a challenge facing nanotechnology. Here the authors design a DNA nanostructure that catalyzes the transport of lipids between bilayers at a rate three orders of magnitude higher than biological enzymes.